Antibacterial Activity Test of the Combination of Citronella Leaf Extract (Cymbopogon nardus L.) and Lime Leaf Extract (Citrus aurantifolia Swingle) Against the Growth of Streptococcus mutans - Aini, Sarifatul; Safutri, Wina; Suswidiantoro, Vicko (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
Dental caries infection is one of the most common dental health problems caused by Streptococcus mutans bacteria. The use of synthetic antibiotics in the treatment of infection risks causing bacterial resistance, so a safer alternative, natural treatment, is needed. Citronella leaves (Cymbopogon Nardus L.) and lime leaves (Citrus aurantifolia Swingle) contain active compounds such as alkaloids, flavonoids, saponins, and tannins that have antibacterial activity. This study aims to determine the effectiveness of the combination of extracts of the two plants against the growth of Streptococcus mutans. The type of research used is laboratory experimental with Completely Randomized Design, consisting of 5 treatments and 4 repetitions. The antibacterial test was carried out by disc diffusion method using a combination concentration of extracts P1 (2.5%: 7.5%), P2 (12.5%: 5%), and P3 18.75%: 2.5%), negative control (distilled water), and positive control (tetracycline). The test results showed that the P3 produced the best inhibition against Streptococcus mutans with an average inhibition zone of (6.02 ± 0.46) mm and fell into the moderate category. Data analysis using the ANOVA test resulted in a significance value of p = 0.000 (p < 0.05), which indicated there were significant differences between treatments. Further tests using Tukey HSD showed that the P3 was significantly different compared to the other treatments. Thus, the combination of citronella and lime leaf extracts is proven to have potential as a natural antibacterial against the growth of Streptococcus mutans bacteria.